Female Sexual Function in Women with Suspected Deep Infiltrating Endometriosis - Ryane Vieira Lima; Ana Maria Gomes Pereira; Fernando Bray Beraldo; Cláudia Gazzo; João Alfredo Martins; Reginaldo Guedes Coelho Lopes (Revista Brasileira de Ginecologia e Obstetrícia, 2018)
Abstract Objective To evaluate the quality of the sexual function of women with suspected deep infiltrating endometriosis. Methods A cross-sectional, observational and prospective study was conducted between May 2015 and August 2016, in which 67 patients with deep infiltrating endometriosis, suspected or diagnosed, were assessed for epidemiological and clinical characteristics, such as pain level through a visual analog scale (VAS), features of deep infiltrating endometriosis lesions and score on the Female Sexual Function Index (FSFI) before the onset of treatment. The statistical analysis was performed using the software STATA version 12.0 (StataCorp LLC, College Station, TX, USA) to compare the variables through multiple regression analysis. Results The average age of the patients was 39.2 years old; most patients were symptomatic (92.5%); and the predominant location of the deep infiltrating lesions was on the rectosigmoid colon (50%), closely followed by the retrocervical region (48.3%). The medianoverallscoreontheFSFIwas23.4;in67.2%of thecasesthescorewas26.5(cutoff point for sexualdysfunction). Deepdyspareunia(p = 0.000,confidenceinterval [CI]:0.64- 0.83) and rectosigmoid endometriosis lesions (p = 0.008, CI: 0.72-0.95) showed significant correlation with lower FSFI scores, adjusted by bladder lesion, patients’ ageand size of lesions. Deep dyspareunia (p = 0.003, CI: 0.49-0.86) also exhibited significant correlation with FSFI pain domain, adjusted by cyclic bowel pain, vaginal lesion and use of gonadotropin-releasing hormone (GnRH) analog. These results reflect the influence of deep dyspareunia on the sexual dysfunction of the analyzed population. Conclusion Most patients exhibited sexual dysfunction, and deep dyspareunia was the pelvic painful symptom that showed correlation with sexual dysfunction.